From Publications to Public Actions: The Role of Universities in Facilitating Academic Advocacy and Activism in the Climate and Ecological Emergency - Gardner, Charlie J.; Thierry, Aaron; Rowlandson, William; Steinberger, Julia K. (Frontiers in Sustainability, 2021)
Thousands of universities have made climate emergency declarations; however the higher education sector is not rising to the collective challenge with the urgency commensurate with scientific warnings. Universities are promoting an increased focus on sustainability through their research, teaching and their own institutional footprints. However, we suggest that such initiatives will be insufficient to catalyse the required transformations in our societies and economies because of i) the time lags inherent in education and research pathways to impact, and ii) their failure to address either real-world political processes or the forces invested in maintaining the status quo. We therefore suggest that academics should move from publications to public actions and engage in advocacy and activism to affect urgent and transformational change. We discuss the barriers to engagement in advocacy that academics face, and propose a number of actions that universities should adopt to help overcome them. These include explicitly recognising advocacy as part of the work mandate of academic staff by altering work allocation models, facilitating engaged research sabbaticals, altering hiring and promotion policies, and providing training to enhance the effectiveness of engagement. In addition, universities must defend the right of academics to engage in protest and push back against emerging threats to academic freedom. Such actions would strengthen a rich tradition of academic protest and enhance the contribution of universities to the public good in areas well beyond sustainability, for example race and social justice (Black Lives Matter, decolonising education) and public health.